Teachers’ Organizations and Educational Reform: Resistance and Beyond - Maharaj, Sachin; Bascia, Nina (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
This paper presents case studies of teacher union-government relationships in three Canadian provinces – British Columbia, Ontario, and Alberta – where teacher organizations have undertaken divergent strategic positions relative to educational reform. It identifies critical factors that may lead teacher unions to challenge government reforms, how and when a teacher organization might instead accommodate governmental reform, and under what circumstances union renewal drives an organization to establish reform strategies of its own. The paper demonstrates the results of these varied strategies and suggests that teacher unions’ stances, including when they are resistant, are rational and, arguably, necessary.